An empirical investigation of purchasing power parity (PPP) for NORDIC countries: Evidence from linear and nonlinear unit root tests - (:unkn) unknown (International Economic Society, 2016)
This article examines the validity of the PPP for NORDIC countries (Denmark, Norway, Sweden and Iceland) through linear and nonlinear unit root tests by using the monthly data of January 2009 – December 2014. It was found out that the real exchange rate series for Iceland were not linear and the real exchange rate series for Denmark, Norway and Sweden were linear. The unit root tests carried out in line with the characteristics of the series indicate that the real exchange rate series in all of the NORDIC countries are not stable. So the empirical findings obtained from this study indicate that the PPP is not valid for NORDIC countries. © International Economic Society.
Keywords: Linear unit root test with structural breaks; Linearity test; Nonlinear unit root tests; NORDIC countries; Purchasing power parity